(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The ways in which the life trajectories and biographies of impoverished people are represented are analyzed, paying attention to their demands and their recognition in society. Firstly, a historical overview of land concentration in Paraná and the consequent uneven urbanization of its capital, Curitiba, which contrasts with the ideal of a model city. It also reveals the intrinsic relationship between the state’s media groups and the dominant interests in land concentration, which hinders the visibility of issues such as access to housing. By bringing together two reports produced in distant temporal contexts, but with the same theme, the vulnerability that affects women without land or housing, the images that compose them exercise political memory, from the perspective of Georges Didi-Huberman.